Hieroglyphic Moth, Diphthera festiva (Fabricius) (Insecta: Lepidoptera: Noctuidae) - James C. Dunford; Kathryn A. Barbara (EDIS)
The hieroglyphic moth, Diphthera festiva (Fabricius), is distributed throughout Florida and tropical or subtropical regions of the New World. The conspicuous larvae often occur gregariously on a wide array of plant species and occasionally are considered pests of pecan, coconut palms, sweet potato and soybeans. This document is EENY-326, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: May 2004.